All Days 1977
DOI: 10.2118/6382-ms
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Use in Calcareous Formations

Abstract: The use of polymers to improve areal and volumetric sweep efficiency of waterfloods in limestone and dolomite reservoirs has been very limited and has seldom achieved the desired results. Anhydrous polymers, used in calcareous formations, have been generally ineffective. A relatively new process has been developed and field tested whereby a monomer solution is mixed and pumped into the formation. Once in place, the well is shut in and the monomer allowed to polymerize in situ. The resultant polymer may polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some experimentalists (Jennings RR, Rogers JH, and West TJ 1971;Smith 1970) claim little or no interrelation between polymer retention and flow resistance. For instance, in calcareous formation, the flow in macro-sized heterogeneity bodies such as thief layers and fractures may not be impacted by permeability perturbation from polymer adsorption on the rock surface (Townsend and Becker 1977). However, others (N. Mungan, Smith, and Thompson 1966;Necmettin Mungan 1969) observed a strong dependency between the two phenomena and attributed the increase in flow resistance that could not be achieved solely by the viscoelastic properties of the solution, to polymer retention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some experimentalists (Jennings RR, Rogers JH, and West TJ 1971;Smith 1970) claim little or no interrelation between polymer retention and flow resistance. For instance, in calcareous formation, the flow in macro-sized heterogeneity bodies such as thief layers and fractures may not be impacted by permeability perturbation from polymer adsorption on the rock surface (Townsend and Becker 1977). However, others (N. Mungan, Smith, and Thompson 1966;Necmettin Mungan 1969) observed a strong dependency between the two phenomena and attributed the increase in flow resistance that could not be achieved solely by the viscoelastic properties of the solution, to polymer retention.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that the irreversibility of polymer retention occurs when adsorption and mechanical entrapments are predominant (D'Angelo, Chertcoff, and Rosen 2003), while reversibility may occur when hydrodynamic entrapment is predominant (Al-Hajri et al 2019). Other studies in the literature, based on coreflood experiments and field observations (Townsend and Becker 1977) experienced partial or total reversibility of polymer retention in dolomite-anhydrite formation after the injection of sufficient chase water. For instance, results showed that after 1.2 PV of injected water, more than 11% of the permeability was recovered.…”
Section: Introductionmentioning
confidence: 99%